Pengaruh Struktur Modal, Ukuran Perusahaan dan Pertumbuhan Penjualan terhadap Nilai Perusahaan pada Perusahaan Farmasi - Anisa Retno Ayu Deyandra; Toto Heru Dwihandoko (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
The company has the main goal of increasing the value of the company as much as possible because maximizing shareholder value is the same as maximizing shareholder wealth. There are several aspects that can affect a company's value, such as capital structure, profitability, company size, dividend policy, leverage, and company growth. The purpose of the study is to identify the influence of capital structure, company size, and sales growth on company value. The population in this study is pharmaceutical companies that have been listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period and 7 samples of pharmaceutical companies were obtained. The type of data used is secondary data that is quantitative. The source of data comes from the annual financial statements. The data analysis in this study used the Multiple Linear Regression Analysis test with the help of the SPSS software application. The results of this study show that the capital structure has a negative and significant influence on the company's value, the size of the company does not affect the company's value, the company's sales growth does not affect the company's value.